2012
DOI: 10.3168/jds.2011-4513
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine milieu and developmental dynamics of ovarian cysts and persistent follicles in postpartum dairy cows

Abstract: Ovarian follicular cysts and persistent follicles are follicular pathologies involved in reduced fertility of dairy cows. Two separate experiments were performed on high-yielding Holstein cows to characterize ovarian cyclicity and evaluate the developmental dynamics of follicle pathologies postpartum. In experiment 1, 58 cows were monitored by ultrasonography twice weekly from d 18±1 to 69±2 postpartum. First ovulation occurred 38±3, 27±2, 20±1, and 25±3 d postpartum in cows with 1 cycle (n=11), 2 cycles (n=21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
2
17
0
6
Order By: Relevance
“…The plasma progesterone concentrations associated with cystic ovaries in this study were similar to those in plasma or milk previously reported in cows with induced or spontaneously occurring cysts (Ribadu et al, 1994;Robinson et al, 2006;Roth et al, 2012;Mutinati et al, 2013;Pusph et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
“…The plasma progesterone concentrations associated with cystic ovaries in this study were similar to those in plasma or milk previously reported in cows with induced or spontaneously occurring cysts (Ribadu et al, 1994;Robinson et al, 2006;Roth et al, 2012;Mutinati et al, 2013;Pusph et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
“…Cyst formation during the early postpartum period (from calving to 60 d postpartum) varies from 6% to 30% [1,5], presumably because of postpartum stress. For instance, lame cows are 2.6 times more likely to develop an ovarian cyst than nonlame cows [3].…”
Section: Introductionmentioning
confidence: 99%
“…The major difficulty in studying the underlying mechanism is that cyst formation can only be retrospectively recognized, after the follicle has undergone extensive pathologic changes. Thus, prediction of pathology formation during follicular development is a formidable challenge [1].…”
Section: Introductionmentioning
confidence: 99%
“…A palpação retal é usualmente utilizada no diagnóstico de cistos foliculares em bovinos; porém, apresenta eficiência moderada para detectar estruturas >25 mm e está sujeita a erros nos casos de estruturas císticas menores (Roth et al, 2012). O diagnóstico conclusivo geralmente é feito com base na identificação da estrutura cística em duas avaliações consecutivas, realizadas com intervalo de dez dias, na ausência de corpo lúteo.…”
Section: Accuracy Of Ultrasound and Behavioral Assessment In Determinunclassified
“…Foram utilizados três rebanhos leiteiros com média de 250 animais em lactação, compostos por animais da raça Girolando, com grau de sangue entre 1/2 e 7/8 Holandês (Roth et al, 2012). Foram registrados o diâmetro médio, em dois eixos perpendiculares, da estrutura cística e a existência ou não de bordo luteinizado (cisto luteinizado) -parede folicular com espessura ≥3 mm e formada por tecido com ecogeinicidade semelhante à de corpo lúteo.…”
Section: Accuracy Of Ultrasound and Behavioral Assessment In Determinunclassified